On dynamics of quantum quadratic operators on M2(C) - Mukhamedov, Farrukh; Mukhamedov, Maksut; Abduganiev, Abduaziz (2010)
In the present paper we study nonlinear dynamics of a class of quantum quadratic operators (q.q.o) acting on the algebra of 2×2 matrices M2(C) .